2016
DOI: 10.3390/nu8070390
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Utilization and Cycling Performance Following Palatinose™ Ingestion: A Randomized, Double-Blind, Controlled Trial

Abstract: (1) Objective: To compare the effects of isomaltulose (Palatinose™, PSE) vs. maltodextrin (MDX) ingestion on substrate utilization during endurance exercise and subsequent time trial performance; (2) Methods: 20 male athletes performed two experimental trials with ingestion of either 75 g PSE or MDX 45 min before the start of exercise. The exercise protocol consisted of 90 min cycling (60% VO2max) followed by a time trial; (3) Results: Time trial finishing time (−2.7%, 90% CI: ±3.0%, 89% likely beneficial; p =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 33 publications
7
37
1
5
Order By: Relevance
“…This mixed finding may be due to different timing and quantities of carbohydrate ingested or the duration, intensity, and type of the exercise protocol [33]. To date, a small number of studies specifically investigated the effects of isomaltulose on performance outcome measures.…”
Section: Sports Nutrition and Cognitive Performancementioning
confidence: 99%
“…This mixed finding may be due to different timing and quantities of carbohydrate ingested or the duration, intensity, and type of the exercise protocol [33]. To date, a small number of studies specifically investigated the effects of isomaltulose on performance outcome measures.…”
Section: Sports Nutrition and Cognitive Performancementioning
confidence: 99%
“…Isomaltulose is a unique carbohydrate known for its slow absorption that results in slow elevations in blood glucose and insulin compared with other carbohydrate beverages (Kawai, Okuda, & Yamashita, ; van Can, IJzerman, van Loon, Brouns, & Blaak, ). Several studies have reported important physiological benefits associated with the consumption of isomaltulose during exercise including the maintenance of blood glucose, increased fat oxidation, and improved exercise performance relative to maltodextrin or sucrose (Achten et al., ; König et al., ). The present study advances our understanding of these physiological benefits, by showing that isomaltulose assists in re‐establishing hydration status following an exercise heat stress without compromising recovery of body core temperature.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize fluid loss, commercial sports beverages that contain a mixture of carbohydrate, such as glucose, fructose and/or maltodextrin, with electrolytes are commonly consumed by athletes, workers, servicemen and others during and following exercise. This is because these beverages help maintain glycaemia and hydration during (Achten, Jentjens, Brouns, & Jeukendrup, ; König, Zdzieblik, Holz, Theis, & Gollhofer, ; Thomas, Erdman, & Burke, ) and following exercise (Evans, Shirreffs, & Maughan, ; Kamijo et al., ; Osterberg, Pallardy, Johnson, & Horswill, ), thereby improving performance and facilitating rehydration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…48.9 ± 10 minutes x 67.4 ± 8.4 minutes, P < 0.05, respectively). In addition to these four studies, another one 21 observed that the low GI group had greater power in the final minutes of sprinting (4.6% increase); however, the authors affirmed that the shortest execution time of the exercise with this intervention is probable (difference of 1.03 minutes), considering the non-statistical finding. Contrary to these, another study 18 evaluated time to exhaustion and observed that the duration of the test was 15% higher in the high GI group after a 4-hour recovery period (86.6 ± 10.7 minutes vs.…”
Section: Brown Et Al (2013) 31mentioning
confidence: 94%